2021
DOI: 10.1002/rcs.2312
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted completion cholecystectomy: A safe and effective approach to a challenging surgical scenario – A single center retrospective cohort study

Abstract: Background: Reoperation following a previous subtotal or aborted cholecystectomy presents a challenging surgical scenario that has traditionally required an open completion cholecystectomy. The aim of this study was to describe an institutional experience with a robotic-assisted approach to completion cholecystectomy. Methods:A database was retrospectively audited to identify all patients who underwent robotic-assisted cholecystectomy performed by two hepatopancreatobiliary surgeons at a single centre from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One study by Tschuor et al reported robotic cholecystectomy in three patients with CDF but does not describe if or how the fistula was treated. 14 videos of intraoperative techniques were not reported in papers reporting robotic CDF closure. A summary of studies is shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study by Tschuor et al reported robotic cholecystectomy in three patients with CDF but does not describe if or how the fistula was treated. 14 videos of intraoperative techniques were not reported in papers reporting robotic CDF closure. A summary of studies is shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of robotic surgery are numerous and include ease of manoeuvring, camera and tool stability, 3D visualisation, better access to small spaces, and improved control 8,11 . Current studies show successful robotic management of bilioenteric fistulas and specifically robotic cholecystectomy with cholecystoduodenal fistula closure, with none of these needing to convert to an open approach 2,11–17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study of 26 patients who underwent robotic-assisted completion cholecystectomy, the mean operative time was 142 min, and the median length of stay was 1 day with one readmission. Three patients experienced minor (Clavien-Dindo ≤ II) complications [ 7 ]. In a case series of robotic-assisted completion cholecystectomy, all three patients initially presented with gangrenous cholecystitis treated with subtotal cholecystectomy to avoid iatrogenic damage to the common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Though a majority of cholecystectomies are performed laparoscopically, a smaller proportion is performed openly. Hence, a new robot-assisted cholecystectomy program is currently being developed [1,2]. Laparoscopic cholecystectomy is a popular and routinely performed procedure in general abdominal surgery worldwide [3].…”
Section: Introductionmentioning
confidence: 99%